An Unusual Complication in Osteonecrosis of Femoral Head: A Case Report - Singaravadivelu Vaidyanathan; Yuvaraja Murugan; Kingsly Paulraj (Case Reports in Orthopedics)
We report a case of fracture of femoral head occurring in the setting of underlying osteonecrosis following a low-energy trauma in a middle-aged male. Patient also has underlying pelvic pathology from a previous trauma. The possible mechanism of injury is discussed. Extensive literature search reveals that this is the first report of a fracture in an osteonecrotic femoral head.